Autophagy regulates fatty acid availability for oxidative phosphorylation through mitochondria-endoplasmic reticulum contact sites - Claudie Bosc (Nature Portfolio, 2020)
How autophagy supports tumor cell metabolism is not fully clear. Here, the authors show that autophagy regulates lipid availability to support mitochondrial oxidative metabolism through mitochondria-endoplasmic reticulum contact sites, necessary for cell proliferation in AML.